2004
DOI: 10.1080/0032472042000272384
|View full text |Cite
|
Sign up to set email alerts
|

Maternal resources, proximity of services, and curative care of boys and girls in Minya, Egypt 1995–97

Abstract: Despite declines in the risk of dying among children in Egypt, girls' excess mortality in early childhood persists. Using data from a representative sample of children in Minya, Egypt, I assess whether maternal resources, marital household structure, and proximity of services influence disparities by sex in curative care. The results show that boys visit any source of care marginally more often than girls. Among children who receive care, boys more often receive private care. Higher maternal education has no e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…Sex is one inherent characteristic of the child which may act as an indicator of the child’s societal status. A study of child curative health-seeking in Minia found that ill girls were less likely to be taken to a medical provider than boys [ 30 ]. Likewise, crude tabulations in the 2008 DHS report showed that compared to girls, slightly higher proportions of boys were taken for treatment (ARI: 77 % and 68 %; diarrhoea: 57 % and 54 %, respectively) [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sex is one inherent characteristic of the child which may act as an indicator of the child’s societal status. A study of child curative health-seeking in Minia found that ill girls were less likely to be taken to a medical provider than boys [ 30 ]. Likewise, crude tabulations in the 2008 DHS report showed that compared to girls, slightly higher proportions of boys were taken for treatment (ARI: 77 % and 68 %; diarrhoea: 57 % and 54 %, respectively) [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…More recent evidence has documented the continued differential treatment of sons and daughters, as well as the increased use of sex-selective abortion in some regions of the world (Arnold et al 2002;Hesketh and Xing 2006). In a band of countries from East Asia through South Asia to the Middle East and North Africa, discrimination against females-through sex-selective abortion, female infanticide, abandonment of newborn girls, and neglect of daughters through differential allocation of food and care-seeking behavior-has resulted in severely imbalanced sex ratios (Li 2004;Yount 2004;Hesketh and Xing 2006).…”
Section: Infant and Child Mortalitymentioning
confidence: 99%
“…For example, in urban China—where the mean age at first marriage and rate of love marriage have increased, fertility has declined, and women's employment is nearly universal—daughters now join or surpass sons in making financial transfers to their parents (Xie & Zhu, 2009). Our focus on material transfers between older parents and their children also adds to the literature on Arab Middle Eastern families, which has focused on intergenerational coresidence (e.g., Khadr & Yount, 2008; Shah, Yount, Shah, & Menon, 2002; Sibai, Yount, & Fletcher, 2007; Yount, 2005Sinunu, Yount, & El‐Afifi, 2008 is an exception), on material transfers between spouses (Hoodfar, 1997), or on material transfers to young children (e.g., Yount, 2001, 2003, 2004a).…”
Section: Discussionmentioning
confidence: 99%
“…At this point, the duties of daughters often have shifted to their husbands' families, whereas those of sons have tended to remain with their natal or biological kin. Because sons have been the most viable forms of old‐age insurance, parents have invested more in sons than daughters (Yount, 2001, 2003, 2004a). Such investments have heightened sons' duties of old‐age support, which have come in the forms of coresidence, material transfers, and wives' instrumental care, especially when sons' parents are widowed or infirm (Yount, 2005).…”
Section: Introductionmentioning
confidence: 99%